Pendidikan Pancasila Sebagai Upaya Membentuk Sikap Toleransi Dalam Masyarakat - Mochammad Alfian Prima Utama; Feila Salasya Ramadila; Annisa Tri Puji Rahayu; Miftahul Jannah; Jessy Nora Sandy; Ari Metalin Ika Puspita (International Forum of Researchers and Lecturers, 2024)
Pancasila education in Indonesia aims to shape the character of a diverse society into a cohesive unity with a focus on the value of tolerance in a multicultural community. This article examines the role of Pancasila education in promoting a tolerant attitude amidst a culturally diverse society, with values such as social justice, unity, equality, and cooperation as the foundation of harmony amidst differences. Studies also indicate the potential to strengthen tolerance values through intercultural interactions, such as in the activity of hunting for takjil, which symbolizes togetherness among various community groups. By strengthening the understanding of Pancasila values, society can be more open and appreciative of differences, creating harmonious intercultural relationships.